Clusterin deficiency is associated with a lack of response to teriflunomide in multiple sclerosis - Malhotra, Sunny; Fissolo, Nicolas; Rodríguez‐Rivera, Carmen; Monreal, Enric; Montpeyo, Marta; Urcelay, Elena; Triviño, Juan Carlos; Pérez‐García, María José; Segura, Miguel F.; Pappolla, Agustín; Río, Jordi; Vilaseca, Andreu; et al. (Clinical and translational medicine, 2024)
Noteworthy, the expression pattern of CLU isoforms detected in non-responders after treatment was more prominent at 12 months since it was not observed at earlier time points (Figure 3E). Since CLU has been reported to mediate processes such as endoplasmic reticulum (ER) stress and autophagy,4 we also explored whether teriflunomide had the potential to induce ER stress and autophagy. SEE PDF] Under conditions like ER stress, the presecreted isoform of CLU can bind to BiP, which stabilizes CLU and facilitates its retrotranslocation to the cytosol and redistribution to mitochondria,6 where CLU inhibits apoptosis.7 Furthermore, the mature secreted CLU isoform can modulate cell proliferation,3 a process inhibited by teriflunomide, particularly in T and B cells with high proliferative rates.8,9 Considering these two CLU-related properties, we evaluated whether the differential expression pattern of CLU isoforms observed between responders and non-responders could translate into differences in the apoptotic and proliferation capacities of T cells from both groups of patients (Table S6 and Figure S8). [...]since mature CLU isoform may egress cells and exert extracellular chaperone activities,10 we measured the serum levels of the mature secreted CLU isoform before and after treatment.